A new occurrence of argentopentlandite and gold from the Au-Ag-rich copper mineralisation in the Paliomylos area, Serbomacedonian massif, Central Macedonia, Greece - MELFOS, V.; VAVELIDIS, M.; ARIKAS, K. (Bulletin of the Geological Society of Greece, 2001)
The Au-Ag-Cu mineralisation in the Paliomylos area is associated with quartz segregations and pegmatoids in the form of boudinaged bodies. The Au, Ag and Cu contents in the ore bodies reach 6.8 ppm, 765 ppm and 0.80 wt%. The ore minerals consist of pyrite, chalcopyrite, sphalerite, pyrrhotite, galena, bismuthinite, argentopentlandite, gersdorffite, cobaltite, aikinite, hessite, native bismuth and gold. Pentlandite contains significant amounts in Ag (13.15 wt%), Au (1.59 wt%) and PGM, demonstrating a formula of Fe5.37 Ni2.56 Ag1.03 Ir0.03 S8.01. On the basis of geological, textural and chemical data, the mineralisation in the studied area was formed under high temperatures.